1989
DOI: 10.1016/0168-1591(89)90101-9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of spatial memory in cattle

Abstract: Two studies were conducted to examine spatial memory of cattle. In Study 1, six heifers were trained and observed in a radial-and parallel-arm maze at two levels of complexity. Grain was placed at the end of each arm, and heifers were released individually and allowed to choose arms freely until all grain was consumed. Incorrect choices occurred when heifers entered a previously entered arm. At the 4-arm level, the mean number of correct choices in the first four entrances was 3.83 and 3.60 for the radial and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 11 publications
1
37
1
Order By: Relevance
“…great (Bailey 1988, Bailey et al 1996. It may be that the differences in forage quantity or quality between prairie dog towns and swales on the shortgrass steppe were not sufficiently large for cattle to change their foraging rates.…”
Section: Discussionmentioning
confidence: 99%
“…great (Bailey 1988, Bailey et al 1996. It may be that the differences in forage quantity or quality between prairie dog towns and swales on the shortgrass steppe were not sufficiently large for cattle to change their foraging rates.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, through choice test, it has been demonstrated that a cow, placed in front of a Y-shaped arm, prefers to enter where some food was previously received as a reward (Hosoi et al, 1995) and escape from the arm where restraint was experienced . Other studies pointed out that cows have a good spatial memory and were able to remember the association between the position and the food received (Kovalcik and Kovalcikova, 1986;Bailey et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Cattle have accurate spatial memories (Bailey et al, 1989), and spatial 429 learning is likely to be a critical factor in grazing behavior (Bailey 430 et al, 1996;Laca, 1998). Therefore additional research should be con-431 ducted to understand this candidate gene and its role in influencing cat-432 tle grazing distribution.…”
mentioning
confidence: 98%